Radiation Losses in a Planar Dielectric Waveguide with a Rough Interface between Dielectric Layers - Matievosova, O.H.; Kovalenko, A.V.; Kurashov, V.N. (Ukrainian Journal of Physics, 2012)
Without the weakly guiding fiber approximation, a statistical model of light scattering by a rough surface in a planar dielectric waveguide has been developed. The dependences of radiation losses on the refractive index contrast, the waveguide core thickness, and the correlation characteristics of a scattering surface have been studied. The difference between the scattering of TE and TM modes has been analyzed, and the two-dimensional model was shown to be not suitable for quantitative estimates of losses in the case of TM modes.